Shortcut to harmonization with Australian spectrum licensing. - Whittaker, M.
Governments may facilitate the introduction of new types of wireless communication services through use of a self-regulated spectrum management system known as spectrum licensing. Spectrum licensing is able to break the nexus between the equipment standardization process and obtaining regulatory approval to access spectrum, avoiding delays and effectively harmonizing spectrum use. There are similar trends at play in several countries, and spectrum licensing can have different levels of implementation of the technical framework, even within a single country, depending on the objectives sought and the manner in which those objectives are designed to be achieved within a particular frequency band. Just as the circumstances that seem to block us in our everyday life depend on our framework of assumptions, the possibilities of spectrum licensing also depend on the chosen technical framework. When a framework is fully implemented, the important underlying objectives are to maximize flexibility and certainty for the operation of equipment while minimizing negotiation for the management of interference. Flexibility facilitates the management of change, and certainty creates a stable basis for that change. And, with minimal negotiation, change is faster and cheaper. The Australian case is taken as an example. The 3.4 GHz band has just been auctioned with license conditions that, for the first time, have been designed to allow equitable spectrum access for both point-to-point and mobile-like services
Keywords: 3.4 GHz; Australian spectrum licensing; Radiocommunications Act; Change management; Equipment operation; Equipment standardization; Equitable spectrum access; Frequency band; Government; License conditions; Mobile-like services; Out-of-band interference management; Point-to-point services; Self-regulated spectrum management system; Spectrum use harmonization; Wireless communication services